Morphological plasticity of uceng fish (Nemacheilus spp.): A statistical exploration of water quality influences in East Java’s river - Rahayu, Dwi Anggorowati; Nugroho, Endik Deni; Sulung, Cahya Ajeng Valenta Tresna; Rusdianto, Rusdianto; Mamat, Noorhidayah Binti (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Morphological plasticity in aquatic organisms is an adaptive phenomenon that enables species to respond to changing environmental conditions, particularly in native fish species such as the Uceng fish. This study aims to: (1) describe the morphological variation of the Uceng fish and water quality parameters in three river locations in East Java; (2) analyze the relationship between water quality parameters and the morphological characteristics of the Uceng fish; (3) identify the water quality parameters that most affect morphological variation of fish through PCA analysis; and (4) model the relationship between water quality parameters as independent variables and fish morphological characteristics as dependent variables. This research employed a correlational approach with a cross-sectional comparative design, comparing fish samples from three different geographic locations: Blitar, Pasuruan, and Lumajang. Data analysis was conducted using correlation analysis, PCA, and multiple regression modeling. Measurement of the Morphological Characteristics of the Uceng Fish, Morphometric Measurement (14 characters). The results showed a significant negative correlation (r = -0.155, p = 0.017) between environmental factors and fish morphology, with approximately 33% of the morphological variation explained by the combination of environmental factors (DO, temperature, COD, and TDS). PCA analysis identified DO as the parameter with the strongest positive influence, while temperature, COD, and TDS showed negative effects. These findings emphasize the species’ adaptive capacity and underline the importance of monitoring environmental quality to support biodiversity conservation in increasingly impacted river ecosystems of East Java.